Correlates of Depressive Symptomatology in African American Breast Cancer Patients - Sheppard, Vanessa B. (2013)
PURPOSE: This study assessed the levels of depressive symptomatology in African Americans women with breast cancer compared to those of women without breast cancer and examined demographic, psychosocial, and clinical factors were correlated with depression. METHODS: A total of 152 African American women were recruited from Washington DC and surrounding suburbs. Breast cancer patients (n=76 cases) were recruited from a healthcare center and women without cancer were recruited from health fairs (n=76 comparison). We assessed depression, psychosocial variables (ego strength and social support) and socio-demographic factors from in-person interviews. Stage and clinical factors were abstracted from medical records. Independent sample t-test, chi square test, ANOVA, and multiple regression models were used to identify differences in depression and correlates of depression among the cases and comparison groups. RESULTS: Women with breast cancer reported significantly greater levels of depression (m=11.5 SD=5.0) than women without breast cancer (m=3.9; SD=3.8) (p<.001). Higher cancer stage (beta=.91) and higher age (beta =.11) were associated with depression in the breast patients, explaining 84% of the variance. In the comparison group, ego strength and tangible support were inversely associated with depressive symptoms, accounting for 32% of the variance. CONCLUSIONS: Women with more advanced disease may require interdisciplinary approaches to cancer care (i.e., caring for the whole person). IMPLICATIONS FOR CANCER SURVIVORS: Depression is often under-recognized and under-treated in African American breast cancer patients. Understanding the factors related to depression is necessary to integrate psychosocial needs to routine cancer care to improve survivors’ quality of life.